The anthropology of labor unions - Durrenberger, E. Paul, editor; Reichart, Karaleah S., editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2010)
Presenting ethnographic data and analysis drawn from eight case studies from diverse industries in the United States and abroad, the contributors to The Anthropology of Labor Unions provide a variety of perspectives on this paradox, including discussions of approaches to and findings on the histories, cultures, and practices of organized labor. They also address substantive issues such as race, class, gender, age, generation, ethnicity, health and safety concerns, corporate co-optation of unions, and the cultural context of union-management relationships. The first to bring together anthropological case studies of labor unions, The Anthropology of Labor Unions will appeal to cultural anthropologists, social scientists, sociologists, and those interested in labor studies and labor movements.--Book jacket.
Introduction / E. Paul Durrenberger and Karaleah Reichart -- Miners, women, and community coalitions in the UMWA Pittston Strike / Karaleah Reichart -- Is this what democracy looks like? / E. Paul Durrenberger and Suzan Erem -- With God on everyone's side: truth telling and toxic words among Methodists and organized farmworkers in North Carolina / Sandi Smith-Nonini -- Buying out the union: jobs as property and the UAW / Peter Richardson -- Approaching industrial democracy in nonunion mines: lessons from Wyoming's Powder River basin / Jessica M. Smith -- Small places, close to home: the importance of place in organizing workers / Lydia Savage -- Economic globalization and changing capital-labor relations in Baja California's fresh-produce industry / Christian Zlolniski -- The tobacco trap: obstacles to trade unionism in Malawi / Marty Otañez -- Concluding thoughts / Karen Brodkin -- Afterword / E. Paul Durrenberger and Karaleah Reichart.
Keywords: Labor unions -- History; Labor unions -- Political activity -- History; Labor unions -- United States -- History